Modeling the thickness of vaults in the church of santa maria de magdalena (Valencia, Spain) with laser scanning techniques. - Herráez, José; Navarro, Pablo; Denia, José Luis; Martín, María Teresa; Rodríguez, Jaime (Journal of Cultural Heritage, 2014)
Restoring cultural heritage is an extremely important job due to its immeasurable value. However, it also requires even greater attention in the case of a building. The actions taken on these constructions not only guarantee their preservation from the point of view of their historical value, but they also guarantee their stability as structures. The need to control historic buildings, analyzing their defects and their possible consequences, is decisive in preventing significant damage. This work demonstrates calculating the thickness of vaults in a church. It is easy to determine the interior and exterior 3D geometry of the church using scanner laser techniques. By combining both geometries, it is easy to determine the difference between the interior vaults and the roof of the church. However, the interior of both geometries is completely unknown, and it is not possible to act on their condition for structural consolidation purposes. This work shows the methods used to determine the interior sections of the vault thicknesses by referencing the internal geometry of both models with the interior of the church, using plumb line system scanning. The results obtained show accuracy better than 6 millimeters.